Living with Hepatitis C Virus: A Systematic Review and Narrative Synthesis of Qualitative Literature. (26th April 2017) - Dowsett, Laura E.; Coward, Stephanie; Lorenzetti, Diane L.; MacKean, Gail; Clement, Fiona
Abstract : Background and Aims . The lived experience of HCV has not been well documented in the literature. The aim of this systematic review was to understand the experiences of living with Hepatitis C Virus (HCV). Methods . Five databases were searched from inception until January 19, 2015. Studies were included if they focused on adults diagnosed with HCV; reported experience living with HCV; and described original research. Results . 46 studies were included. Studies found that participants had reduced quality of life due to physical symptoms. Due to physical symptoms and discrimination, many participants switched to part-time work or quit their jobs. Many individuals reported negative experiences with the healthcare system; themes of feeling unsupported, not having adequate information, and not feeling involved in decisions were reported. Stigma significantly impacted those living with HCV. Conclusions . Published literature indicates that those with HCV often feel stigmatized and unsupported in their care, relationships, and work environments, while simultaneously coping with physical and psychological symptoms. This synthesis points to areas where greater education, compassion, and patient-centered healthcare could improve the experience of people living with HCV.